Highly‐Tunable Intrinsic Room‐Temperature Ferromagnetism in 2D van der Waals Semiconductor CrxGa1−xTe. Issue 1 (27th October 2021) - Zhang, Gaojie; Wu, Hao; Zhang, Liang; Zhang, Shanfei; Yang, Li; Gao, Pengfei; Wen, Xiaokun; Jin, Wen; Guo, Fei; Xie, Yuanmiao; Li, Hongda; Tao, Boran; et al.
Abstract: The combination of semiconductivity and tunable ferromagnetism is pivotal for electrical control of ferromagnetism and next‐generation low‐power spintronic devices. However, Curie temperatures ( T C ) for most traditional intrinsic ferromagnetic semiconductors (≤200 K) and recently discovered two‐dimensional (2D) ones (<70 K) are far below room temperature. 2D van der Waals (vdW) semiconductors with intrinsic room‐temperature ferromagnetism remain elusive considering the unfavored 2D long‐range ferromagnetic order indicated by Mermin–Wagner theorem. Here, vdW semiconductor Cr x Ga1− x Te crystals exhibiting highly tunable above‐room‐temperature ferromagnetism with bandgap 1.62–1.66 eV are reported. The saturation magnetic moment ( M sat ) of Cr x Ga1− x Te crystals can be effectively regulated up to ≈5.4 times by tuning Cr content and ≈75.9 times by changing the thickness. vdW Cr x Ga1− x Te ultrathin semiconductor crystals show robust room‐temperature ferromagnetism with the 2D quantum confinement effect, enabling T C 314.9–329 K for nanosheets, record‐high for intrinsic vdW 2D ferromagnetic semiconductors. This work opens an avenue to room‐temperature 2D vdW ferromagnetic semiconductor for 2D electronic and spintronic devices. Abstract : 2D van der Waals (vdW) semiconductor Cr x Ga1− x Te with highly tunable intrinsic room‐temperature ferromagnetism is realized and shows robust room‐temperature ferromagnetism with the 2D quantum confinement effect, enabling T C record‐high 314.9–329 K for 2D semiconductors. The M sat of vdW Cr x Ga1− x Te crystals can be effectively tuned up to ≈5.4 times by controlling Cr concentration and up to ≈75.9 times by changing the thickness.